(untitled) (Journal of Informatics Education and Research, 2024)
The impact of Partition still lingers in the minds of people in India today. Every incident is viewed through the lens of religion and caste. Political, monetary, and selfish motives often ignite this communal fire. Mohini Kent’s novel ’Black Taj’ vividly portrays the enduring impact of Partition on the people of post-independence India, particularly on women like Simi who grapple with the trauma and prejudices passed down through generations. Through Simi and Imran’s star-crossed love story, Kent skillfully navigates the societal barriers and communal conflicts that continue to afflict India, echoing the sentiments of many who still bear the scars of Partition. Kent’s poignant portrayal serves as a compelling reminder of the deep-rooted wounds that persist, fueling the ongoing communal tensions in contemporary India.